Peran Instagram sebagai Platform Digital Marketing dalam Meningkatkan Daya Saing Penjualan UMKM di Siwalankerto - Dawiyah, Salsabillah Al; Takarini, Nurjanti (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Micro, small, and medium enterprises (MSMEs) are increasingly relying on social media as a marketing tool, thanks to the expansion of digital technology. The purpose of this study was to analyze how Startias Cake Cookies, an MSME in the Siwalankerto area, has been using Instagram to increase sales and compete with other local businesses. Using the Community-Based Participatory Research (CBPR) paradigm, the implementation of service can be described as a mentoring process through active qualitative data collection, where the service team not only observes but is also directly involved in monitoring and documenting partners' marketing efforts on Instagram @startiascakecookies. Instagram increases the intensity of product promotions, customer engagement, marketing reach, and consumer buying interest. Instagram, as a digital marketing platform, also helps build a stronger corporate reputation. Therefore, with regular management and consideration of product attributes, Instagram can be a powerful marketing tool for MSMEs.